A Comparative Study According to Angiotensin Genetic Diversity As Indicator for 30m Freestyle Swimming in Youth aged (15 – 16) Year Old - Khalid, Ghezwan; Adeeb, Ghasan (Journal of Physical Education, 2021)
The orientation process done by coaches and academicians in swimmers’ selection was based on apparent indicators and somebody and physical indicators. Yet the development in genetic studies and applying it to each swimmer will be more accurate. The researchers aimed at studying the athlete’s genes, performance genes based on genetic studies so as to compare among the three versions of the gene and matching it to the corresponding physical abilities. This study sheds the light on swimmers’ orientation and selection through comparing genes a matter that can help specify what is suitable for 30m freestyle swimmers.